The Effect of Entrepreneurship Orientation on Entrepreneurial Intention among Undergraduate Students in Malaysia - Al-Hussain Abdullah Al-Suraihi; Walid Abdullah Al-Suraihi; Norailis Ab Wahab (Asian Scholars Network, 2024)
Non-Indexed Publication